1993
DOI: 10.1088/0256-307x/10/4/008
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Measurement of the Photoionization Cross Section of the Excited 7pState of Potassium

Abstract: Tbe absolute photoionization cross section for tbe excited 7p state of K has been measured using the method of ionization saturation. The measured cross sections u , ~ (321.8nm) and uTP (643.6nm) are (0.9f0.6) M b and (1.9f0.9) Mb, respectively. Tbe results are in good agreement with the calculated values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In figure 5 we show the existing experimental and theoretical calculations of the photoionization cross-sections from the 7p excited state ss a function of ionizing laser wavelengths. The solid line represents the theoretical data obtained from the published curve of the data reported by Aymar et al [6], solid circle is the experimental data reported by Feng and Zhang [17] whereas the solid squares are the present experimental results. Evidently, all the experimental data points lie on the theoretically calculated curve.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In figure 5 we show the existing experimental and theoretical calculations of the photoionization cross-sections from the 7p excited state ss a function of ionizing laser wavelengths. The solid line represents the theoretical data obtained from the published curve of the data reported by Aymar et al [6], solid circle is the experimental data reported by Feng and Zhang [17] whereas the solid squares are the present experimental results. Evidently, all the experimental data points lie on the theoretically calculated curve.…”
Section: Resultsmentioning
confidence: 84%
“…Burkhardt et al [16] determined the photoionization cross-sections and atomic densities for the resonance levels of sodium, barium and potassium using the saturation technique. Feng and Zhang [17] measured the photoionization cross-section from the 7p excited state whereas, Amin et al [18] reported the photoionization cross-sections from the 4p, 5d and 7s excited states using the saturation technique in conjunction with a thermionic diode ion detector. Borovick [19] measured the autoionization cross-section of potassium atoms excited by electron impact in the energy range from 18.72 to 202 eV.…”
Section: Introductionmentioning
confidence: 99%